Comorbidity of mefv gene mutation and Henoch-Schoenlein purpura. - Türkoğlu, Z.; Kavala, M.; Can, B.; Südoğan, S.; Zindanci, I.; Koc, M. (European Journal of Pediatric Dermatology, 2009)
Henoch-Schoenlein purpura (HSP) is the most common acute vasculitis of childhood, including purpuric rash occuring on the lower extremities, gastrointestinal symptoms, renal involvement and arthritis. HSP is rarely associated with one of the hereditary periodic fever syndromes such as hyperimmunoglobulinemia D and familial Mediterranean fever (FMF). Approximately 5% of individuals with FMF have been reported to have HSP. We report an 8-year-old male child who has Mediterranean fever (MEFV) gene mutation and purpuric rash with abnormal IgA and IgM deposits visualized by immunofluorescence technique.